Evaluation of Ovarian Reserve Tests in Women with Systemic Lupus Erythematosus. (10th April 2014) - Ulug, Pasa; Oner, Gokalp; Kasap, Burcu; Akbas, Emin Murat; Ozcicek, Fatih
<x xml:space="preserve">Abstract</x> Objective Impact of systemic lupus erythematosus (SLE) on fertility may be negative, and ovarian function can be also reduced by autoimmune oophoritis. In this article, we evaluated the ovarian reserve of pre‐menopausal women firstly diagnosed with systemic lupus erythematosus (SLE). Methods This was a prospective controlled study which included twenty women with SLE and twenty healthy women as controls in the reproductive age. Basal levels of FSH, estradiol (E2), and LH on cycle day 3 were measured. All participants underwent transvaginal ultrasonographic examination on the third day of their menstrual periods for the determination of ovarian volume (OV) and total antral follicle count (AFC). Results A significant difference in FSH, LH, and E2 levels was observed between women with SLE and healthy controls. There was a statistically significant reduction in total AFC and OV in SLE group. Age was associated negatively with AFC, whereas positively with FSH and LH. Menstrual irregularity was significantly higher in SLE patients than control. AFC was the most reliable test to show the menstrual irregularity and negatively correlated each other in women with SLE. Conclusion In this preliminary study, the first in SLE patients, we illustrated that women with SLE had lower ovarian reserves and higher menstrual irregularity compared with healthy controls according to hormonal and ultrasonographical evaluation.